Economic Impacts of Inadequate Sanitation in Pakistan - World Bank (Washington, DC, 2014)
In Pakistan, the deterioration of the environment continues to harm livelihoods and health, increasing the vulnerability of the nation's poor. It has long been clear that lack of access to clean water and sanitation facilities has a wide variety of impacts; however, the data and evidence needed to verify the size of the burden imposed on the people of Pakistan are limited. As a result, investment in the water and sanitation sector remains well below what is required to ensure for the population a basic minimum of services. Indeed, Pakistan's population is projected to grow by more than 2.9 percent a year, which means an additional 4.0 million people each year who will require additional clean water and sanitation facilities. The Water and Sanitation Program undertook this study to conduct evidence based research to help advocacy in the sanitation sector. The study aims to empirically estimate the economic impacts of current poor sanitation conditions in Pakistan as well as the economic benefits of options for improved conditions. The study's ultimate goal is to provide policy makers at both national and local levels with evidence to justify larger investments in improving the sanitation conditions in the country. It also provides recommendations, again based on empirical evidence, for effectively planning and implementing sustainable sanitation and hygiene programs.